Sex preference and its association with reproductive behavior among pregnant women attending antenatal clinic in a teaching hospital, Pokhara - Gurung, Nirsuba; Singh, Sakun (Journal of Chitwan Medical College, 2020)
Background: Nepal is basically having patriarchal societies where men are considered as a head of family and society. Gender discrimination is one of the major problems in the Nepalese society which adversely affects women health and development. So, the study aimed to find out sex preference among the pregnant women and how it affects reproductive behavior like use of family planning, abortion and fertility intension. Methods: A cross-sectional descriptive study was carried out in Gynecology and Obstetrics outpatient department (OPD) of a Teaching Hospital in Pokhara. A total of 272 pregnant women were recruited through convenient sampling technique. Data collection was done by face to face interview. Data was entered in MS-Excel 2007 and analyzed in SPSS version-16. Chi-Square was used to find out the association between variables. Results: The mean age of the pregnant women were 25.51 years. Almost all the respondents were literate and 69(62.1%) of them were unemployed. More than half (57%) of the respondents had never used any method of family planning. Among 272 respondents 59(21.7%) of them had son preference which was significantly associated with age (p-value-0.028), educational level (p-value-0.000), and history of abortion (p-value-0.029). Conclusions: Despite of increasing education level of women still one third of the women had sex preferences. Sex preferences leads to decrease use of family planning, increased abortion rate and high parity which affects health of the women. It was observed that reproductive behavior is relatively affected by sex preferences.